EVALUASI KEBIJAKAN SISTEM E-KINERJA TERHADAP APARATUR SIPIL NEGARA PADA SUKU DINAS PENANGGULANGAN KEBAKARAN DAN PENYELAMATAN KOTA ADMINISTASI JAKARTA UTARA - hani, dwibi; Firman, Firman (JOURNAL OF GOVERNMENT (Kajian Manajemen Pemerintahan dan Otonomi Daerah), 2019)
The research has a purpose for knowing how to apply of e- governmnet that explains about Evaluation of e-kinerja system towards the civil servants in fire and disaster relife Office in Administration City of North Jakarta, by there is a change of the most new system in implementing e-kinerja that has useful result for civil servants that can be improved of their working performance is more better. Regional Personal Agency of DKI Jakarta Province is able to improve the working performance of civil servants through implementing e-kinerja, in this research, the researcher uses Evaluation Policy Theory by Said Zainal Abidin ( 2012 ) and e-Government theory by Richardus Eko Indrajit ( 2006 ). The method of result that be used descriptive qualitative method, the resaerch finds that the application of e-Kinerja in Sub-service of Prevention and Rescue Service in Administartion City of North Jakarta has been formed successful. The application of e-Kinerja is able to change the working performance of civil servants more better in addition their working responbility each employees, but when its implementation has still some obstacles. In implementing e-kinerja, this is the important of supervision to a leader because it’s very influential towards employees in order that more have awarness employees towards duty’s resposibility, the perforce carries out positive effects for civil servants become country’s servants that can be competed supportively. And becoming civil servants that are discipline, responsible, and can do all activities nicely.